Nutritional value of wild, cultured and frozen prawn Macrobrachium rosenbergii (De Man, 1879) - Ferdose, A; Hossain, MB (International Journal of Natural Sciences, 2011)
This investigation principally entails with the proximate analysis of the constitutional composition of fresh water prawn, Macrobrachium rosenbergii. Protein, fat, moisture, ash and carbohydrate content in prawn collected from wild, culture farm and market (frozen form) during April, 2010 were determined dry matter basis by following AOAC method to evaluate the nutritional value of prawn from different sources. The proximate composition of the muscle tissue of wild, cultured and frozen prawn were found to be 68.27 ± 0.23, 74.85 ± 0.65 and 60.8 ± 0.12% protein; 6.99 ± 0.92, 5.61 ± 0.37 and 8.21 ± 0.14 % carbohydrate; 8.44 ± 0.10, 9.15 ± 0.61 and 7.89 ± 0.005% lipid; 16.30 ± 0.65, 10.14 ± 0.55 and 23.09 ± 0.39% ash; 78.3 ± 5.83, 77.1 ± 1.69 and 74.9 ± 0.98% moisture respectively. Prawns collected from all sources showed reasonably good proximate composition although variation occurred. This indicates that the wild has also provided with adequate food. The proportion of total protein and lipid were found to be higher in cultured prawns than in the others. In contrast, the proportions of ash contents were higher in frozen prawns when compared with other two, and moisture contents were higher in wild and cultured prawn. In the present study, nutrition wise, the adult cultured prawn was better compared to the wild and frozen prawn. Since M. rosenbergii is a good source of protein, and very low in fat, it can be used as a healthy choice of food for human consumptions. Key words: Proximate composition; freshwater prawn; Macrobrachium rosenbergii; nutritional value. DOI: http://dx.doi.org/10.3329/ijns.v1i2.8821 International Journal of Natural Sciences (2011), 1(2):52-55